Pregestimil: prescribing borderline substances (May 11, p. 38). Issue 13 (22nd June 1973) - Unknown
Abstract : We unwisely said that a general practitioner needs a consultant's letter to justify the prescription of Pregestimil or a similar borderline substance. Officially no such letter is needed, but we feel that, especially in the case of a rare disease, it can help to ensure that the patient gets the treatment without administrative trouble.